Did Securitization Fail to Contain the Covid-19 Pandemic? The Case of Greece - Lampas, Nikolaos (HAPSc Policy Briefs Series, 2020)
In response to the COVID-19 Pandemic many European governments responded by securitizing the pandemic and adopting a series of emergency measures in order to curb the spread of the pandemic. However, in most cases the measures were unsuccessful. Does this constitute a failure of securitization? In order to address this question, we will analyze the case of Greece. The case of Greece is particularly interesting because it was one of the first countries to adopt emergency measures and for a time it was heralded as a success story in countering the effects of the pandemic. According to the findings of this brief, the case of Greece does not constitute a failure of securitization. The Greek government did show a degree of inconsistency in its efforts of securitizing the pandemic but that was consistent with the fluctuation of the number of confirmed cases and COVID-19 related deaths and the impact of the pandemic on the Greek economy and attitude of the general population.